Level of Knowledge and Extent of Adoption of Farmers on Recommended Tuberose Production Practices - Shubhadeep Roy, Rekha Bhagat, (Indian Journal of Extension Education, 2022)
The study was conducted in Nadia district ofWestBengal with 80 tuberose growers tomeasure the level of knowledge and extent of adoption of the recommended tuberose production practices among the farmers.Most of the respondents were found to belong tomediumlevel of knowledge and adoption category. Knowledge level and extent of adoption had shown some significant correlations with extension agency contact and mass media exposure, From the study it was clear that extension agencies have to bemore active to enhance the knowledge level and extent of adoption of the flower growers.